The effect of isorhamnetin glycosides extracted from Opuntia ficus-indica in a mouse model of diet induced obesity1. Issue 3 (11th March 2015) - Rodríguez-Rodríguez, César; Torres, Nimbe; Gutiérrez-Uribe, Janet A.; Noriega, Lilia G.; Torre-Villalvazo, Iván; Leal-Díaz, Ana M.; Antunes-Ricardo, Marilena; Márquez-Mota, Claudia; Ordaz, Guillermo; Chavez-Santoscoy, Rocío A.; Serna-Saldivar, Sergio O.; Tovar, Armando R.
<x xml:space="preserve">Abstract</x> An OFI extract rich in isorhamnetin glycosides prevents metabolic abnormalities associated with DIO.